ROLE OF PUBLIC EXTENSION AND ITS EFFECT ON AGRICULTURE PRODUCTIVITY: AN INSIGHT FROM INDIAN NATRUAL RUBBER CULTIVATION - Resmi C.P; Karthika P Devan; Rajalakshmi. A; Raji Mohan (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Public extension activities are considered an indispensable part of Indian agricultural strategy. The only way to achieve tremendous progress in production and productivity is through effective adoption of scientific agro-practices among farmers. Government has taken several grass root level initiatives in order to strides the level of adoption of modern innovation in farm fields. This paper analysed the effectiveness of various extension services of Rubber Board of India on productivity enhancement of natural rubber cultivation. The study has taken small natural rubber growers in India. The analysis reveals that the Rubber Board of India has played remarkable role in expansion of production as well as productivity of natural rubber in India. JEL Classification: Q